Staying safe while staying together: the COVID‐19 paradox for participants returning to community‐based sport in Victoria, Australia. (11th November 2021) - Staley, Kiera; Seal, Emma; Donaldson, Alex; Randle, Erica; Forsdike, Kirsty; Burnett, Donna; Thorn, Lauren; Nicholson, Matthew
Abstract: Objective : To identify the challenges adult community sport participants anticipate when returning to sport in Victoria, Australia, post a COVID‐19 shutdown. Methods : Using online concept mapping, participants brainstormed challenges to returning to community sport, sorted them into groups and rated them for impact and ability/capacity to overcome. Analysis included multidimensional scaling and hierarchical cluster analysis. Results : Forty‐five community sport participants representing 24 sports identified 69 unique challenges to returning to sport. Eight clusters/questions participants need answered emerged from the sorting data (mean cluster impact and ability/capacity rating out of 5): Will we have enough participants? (3.32, 2.89); How do we stay safe? (3.31, 3.35); How will our sport change? (3.17, 2.85); How can we stay together? (3.15, 3.01); Will I be physically ready? (3.15, 3.05); What about the money? (2.86, 2.53); What about me? (2.65, 3.13); and What about the facilities? (2.49, 2.45). Conclusions : Participants perceived paradoxical challenges to returning to sport after COVID‐19 shutdown, which revolved around staying safe, staying connected and accessing meaningful sport activities. Implications for public health : Sport organisations and public health practitioners should address the participant‐centred challenges identified in this study to maximise the public health benefits of participants returning to community sport.